Practical power distribution for industry - De Kock, Jan.; Strauss, Cobus (Amsterdam ; Boston : Newnes/Elsevier, 2004)
The book provides technical know-how not covered by most universities and colleges in a subject that is central to the roles of many electrical engineers in industry, focusing on switchgear, power cables, power factor correction, and network studies. *Learn how to install and maintain electrical power equipment in industrial settings *Select and specify the right power system at the right price *Provides the practical essentials for reliable operation of industrial electrical networks - covering switchgear, cabling and power correction factors.
Introduction & Definitions, Fundamentals of Power Distribution, Short-circuit current calculations, Medium Voltage Switchgear, Power Cables, Transformers, Compensation and Power Factor Correction, Grounding, Overview of Computer Simulation Software, Latest Developments in Technology.
Includes index.
Keywords: Electric power distribution; Industries -- Power supply; Electronic books